Corporate criminal liability in English law - Sepioło-Jankowska, Iwona (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
Juridical regimes have been created in order to punish corporate wrongdoing. Although the imposition of criminal liability on corporations, as opposed to managers or employees, has generate considerable debate, commentators have not comprehensively analyzed why corporate criminal liability exists. Furthermore, it is not clear that corporate criminal liability is the best way to influence corporate behavior. Following sections will try to find answers to the above mentioned questions.